2023
DOI: 10.3390/su15021551
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Ecotourists’ Perceived Authenticity and Perceived Values on Their Behaviors: Evidence from Huangshan World Natural and Cultural Heritage Site

Abstract: Drawn to the unique natural and geographical advantages of ecotourism scenic areas, tourists can roam the natural environment and, at the same time, promote the sustainable development of the scenic area’s ecology. As a result, ecotourism has gradually become a popular type of tourism. Tourists’ perceived authenticity, perceived values, revisit intentions, and environmentally responsible behaviors, which are important variables in understanding their cognition and behaviors, have received extensive attention f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 132 publications
0
2
0
Order By: Relevance
“…Moreover, research studies combining ecotourism, PEB, and PV of visitors are rare. Exceptionally, few studies were able to reveal that PEB is influenced by the PV related to ecotourism [12,[46][47][48]. However, the influence of PEB on PV remains unexplored, especially when combined with ecotourism while focusing on domestic PEB, which the current study sought to investigate.…”
Section: H5 Motivation Positively Influences Pvmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, research studies combining ecotourism, PEB, and PV of visitors are rare. Exceptionally, few studies were able to reveal that PEB is influenced by the PV related to ecotourism [12,[46][47][48]. However, the influence of PEB on PV remains unexplored, especially when combined with ecotourism while focusing on domestic PEB, which the current study sought to investigate.…”
Section: H5 Motivation Positively Influences Pvmentioning
confidence: 97%
“…Chiu et al [47] also identified the positive influence of PV on environmentally responsible behavior in ecotourism, using SEM. Furthermore, Yang et al [48] revealed that PV positively influences post-tour PEB and revisit intentions of ecotourists visiting the Huangshan World Natural and Cultural Heritage Site. Furthermore, Murphy et al [49] employed PLS-SEM to investigate positive experiences with elements of the destination's macro-environments, and revealed that service infrastructure positively affected perceptions of trip value.…”
Section: The Relationship Of Environmental Behavior Environmental Kno...mentioning
confidence: 99%
“…Authenticity concerning tourist objects and destinations, along with tourist experiences, has been previously studied [24,25]. In heritage tourism, authenticity could be considered the most essential feature of a destination [4].…”
Section: Authenticitymentioning
confidence: 99%
“…Thus, the concept of constructed authenticity, also known as "perceived authenticity", was adopted for this study. While researchers have examined authenticity in different tourism settings, such as ecotourism [25], heritage tourism [28,29], and rural tourism [30], research on how authenticity affects heritage tourists' experiences is minimal.…”
Section: Authenticitymentioning
confidence: 99%
“…Second, it provides socio-economic benefits for communities living in tourist destinations [10]. Third, it conserves cultural heritage and creates authentic tourism experiences [20]. Thus, more research is needed to explore how PEBs are promoted among tourists and how to measure their effectiveness in promoting sustainable tourism practices [4,13].…”
Section: Introductionmentioning
confidence: 99%